2018
DOI: 10.3389/fncel.2018.00103
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Function Modulates the Effects of Long-Chain Polyunsaturated Fatty Acids on the Mouse Cerebral Cortex

Abstract: Different dietary ratios of n−6/n−3 long-chain polyunsaturated fatty acids (LC-PUFAs) may alter brain lipid profile, neural activity, and brain cognitive function. To determine whether ovarian hormones influence the effect of diet on the brain, ovariectomized and sham-operated mice continuously treated with placebo or estradiol were fed for 3 months with diets containing low or high n−6/n−3 LC-PUFA ratios. The fatty acid (FA) profile and expression of key neuronal proteins were analyzed in the cerebral cortex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 94 publications
3
12
2
Order By: Relevance
“…Synapsins are a family of presynaptic proteins that play critical roles in synaptic development, neurotransmitter release, and neural plasticity through phosphorylation-dependent processes (Chi et al, 2003;Menegon et al, 2006;Giachello et al, 2010). Considering the roles of PI3K, PSD95, and synapsin, our results suggest that diets enriched in n-3 LC-PUFA and with different ratios of specific n-6 and n-3 PUFAs modulate the expression of key elements involved in neuroprotective signaling and synaptic transmission in AD mice, consistent with previous reports on the effects of DHA-enriched diets on hippocampal neuronal development (Cao et al, 2009), synaptic function (Cao et al, 2009), synaptic membrane proteins (Calon et al, 2004;Cansev et al, 2008;Sidhu et al, 2016;Herrera et al, 2018), and the restoration of neural plasticity and cognition after brain trauma (Wu et al, 2011). Our present findings indicate that two diets differing in their specific ARA, EPA, DPA, and DHA content, and in the n-6/n-3 PUFA ratio induce divergent changes in the lipidome of AD mouse brains.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Synapsins are a family of presynaptic proteins that play critical roles in synaptic development, neurotransmitter release, and neural plasticity through phosphorylation-dependent processes (Chi et al, 2003;Menegon et al, 2006;Giachello et al, 2010). Considering the roles of PI3K, PSD95, and synapsin, our results suggest that diets enriched in n-3 LC-PUFA and with different ratios of specific n-6 and n-3 PUFAs modulate the expression of key elements involved in neuroprotective signaling and synaptic transmission in AD mice, consistent with previous reports on the effects of DHA-enriched diets on hippocampal neuronal development (Cao et al, 2009), synaptic function (Cao et al, 2009), synaptic membrane proteins (Calon et al, 2004;Cansev et al, 2008;Sidhu et al, 2016;Herrera et al, 2018), and the restoration of neural plasticity and cognition after brain trauma (Wu et al, 2011). Our present findings indicate that two diets differing in their specific ARA, EPA, DPA, and DHA content, and in the n-6/n-3 PUFA ratio induce divergent changes in the lipidome of AD mouse brains.…”
Section: Discussionsupporting
confidence: 91%
“…We previously found that different concentrations of n-6 and n-3 LC-PUFAs in the diet are associated with differences in the total fatty acids (FAs), sphingolipids, and gangliosides in the female mouse cerebral cortex. Interestingly, these changes in the brain lipidome composition are partially dependent on the presence or absence of circulating ovarian hormones (Herrera et al, 2018). Furthermore, we also found that diet and ovarian function interact and affect the expression of several neuronal proteins as well as the APP levels in the brain.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations